Lodo industrial têxtil como adsorvente alternativo na adsorção e dessorção de azul de indigotina e vermelho ponceau em solução aquosa mono e multicomponente - Pereira, Izadora Consalter (2024)
The presence of dyes in water and effluents has raised concern regarding the inefficiency of conventional treatments and the risks associated with the inappropriate disposal of these pollutants. Adsorption and desorption of dyes Indigotin blue (AI) and Ponceau red (VP) in aqueous solution and in mixture were evaluated using textile sludge as an alternative adsorbant to high-cost commercial activated carbons. Sludge in natura (LTI), after thermal teatment (LTP) and chemical treatment (LTF) were characterized by textual and physico-chemical analyses. Kinetic, isotherm and thermodynamic assays were conducted under the optimal conditions obtained in the statistical planning with central composite rotational design (CCRD), varying pH, mass of adsorbent, and stirring speedfor adsorption and desorption in batch assays. In fixedbed column, adsoption was studied under variation of influent flowrate, concentration of dyes in mixture, and mass of adsorbent accoding to CCRD method. Thermal and chemical activation increased the surface area of the adsorbents, increasing the adsorption capacity. The removal efficiencies under optimal conditions in LTI, LTP and LTF resulted in 31.51%, 98.84% and 96.63% for AI and 33.98%, 99.94% and 97.82% for VP, respectively. The PSO model best represented the adsorption for LTI with AI (0.773 mg g-1; pH 3.6) and with VP (0.997 mg g-1; pH 3.6). The PSO model better represented the adsorption for AI (2.93 mg g-1; pH 2.0) and VP (3.10 mg g-1; pH 3.6) with LTP, respectively, and for LTF with AI (2.95 mg g-1; pH 2.0). The PPO model best adjusted the VP data (3.23 mg g-1; pH 2.0) with LTF. In the adsorption isotherms, the Langmuir model stood out for LTI with AI and VP. The Freundlich model best represented the adsorption for LTP and LTF with both dyes. Regarding desorption kinetics, desorption capacities were obtained for LTI with AI and VP of 03679 and 0.4394 mg g-1, respectively, for LTP of 1.6069 mg g-1 with AI and for LTP of 1.8013 mg g-1 with VP. For LTF, the desorption capacities were 2.0422 and 2.1884 mg g-1 for the AI and VP dyes, respectively, with better fits to the PSO model. The desorption isotherm tests revealed better fits to the Sips model for the three adsorbents with AI and VP. Adsorption and desorption (in LTI, LTP and LTF) presented spontaneous reactions of an endothermic (adsorption) and exothermic (desorption) nature, both thermodynamically favorable. In tests with the fixed bed column, the optimal conditions for influent flow and adsorbent mass were obtained for LTP (0.7075 g and 3.35 mL min-1) and LTF (0.2927 g and 6.20 mL min-1), respectively. In this way, it is concluded that the alternative adsorbents LTP and LTF were satisfactory in the adsorption and desorption capacity of the dyes studied.